Oral Mucositis-Related Oropharyngeal Pain and Correlative Tumor Necrosis Factor-α Expression in Adult Oncology Patients Undergoing Hematopoietic Stem Cell Transplantation - FalI-Dickson, Jane M.; Ramsay, Edward S.; Castro, Kathleen; Woltz, Patricia; Sportés, Claude (Clinical therapeutics, 2007)
Background: Oral mucositis is the most common sequela of conditioning chemotherapy (CT) for hematopoietic stem cell transplantation (HSCT) and is the principal cause of most of the associated pain. Tumor necrosis factor-α (TNF-α) is a key pathogenic component of oral mucositis. Objectives: The primary purpose of this study was to describe oral mucositis-related oropharyngeal pain in the setting of HSCT. A secondary purpose was to assess the effectiveness of molecular biology methods for measuring TNF-α concentrations in plasma, saliva, and buccal epithelial cells in patients with oral mucositis undergoing HSCT. Methods: This descriptive, correlative study recruited subjects aged ≥ 18 years who were scheduled to receive HSCT with CT. Subjects assessed their pain at baseline and 9 days (±24 hours) after CT using a pain visual analog scale (VAS) from 0 = no pain to 10 = worst possible pain, as well as word descriptors of sensory and affective pain. The extent and severity of oral mucositis were evaluated using the Oral Mucositis Assessment Scale. Saliva and blood samples and buccal brush biopsies were obtained at the same time points. Salivary and plasma TNF-**α concentrations were measured using an enzyme-linked immunosorbent assay. Quantitative real-time polymerase chain reaction testing was used to measure buccal TNF-α gene expression. To determine the optimal method of RNA isolation, samples were extracted using 3 different methods: TRIzol, RNeasy, and RLT/TRIzol. Results: Twenty-five adult men and women (mean age, 46 years; age range, 32-68 years; 64% white) underwent HSCT with CT. Significant differences from baseline to day 9 were observed in the severity of oral mucositis ( P < 0.001), the overall intensity of oral pain ( P < 0.05), the overall intensity of oral pain with swallowing ( P < 0.01), the sensory dimension of oral pain with swallowing ( P < 0.05), and the sensory and affective dimension of oral pain with swallowing ( P < 0.05). The severity of oral mucositis was significantly associated with the overall intensity of oral pain ( P < 0.05). Although mean scores for oral pain were low, 8 subjects had clinically unacceptable pain VAS scores (>3) while receiving opioids. Fourteen subjects had measurable increases in buccal TNF-α RNA expression at day 9 ( P = 0.027 vs baseline), as measured using the TRIzol method, which was found to be the best method for measuring this variable. TNF-α RNA content in buccal samples was significantly associated with the worst intensity of oral pain with swallowing (partial R 2 = 0.19; P < 0.05). Conclusions: Despite the use of opioids, oropharyngeal pain remained a treatment challenge in approximately one third of these subjects after CT with HSCT. The sensitive assay used to measure TNF-α gene expression in buccal cells may be useful in investigating molecular events in oral mucositis-related pain, as well as in evaluating the therapeutic response to investigational agents.